Serum D‐lactate concentrations in dogs with parvoviral enteritis - Emilee C. Venn; Alex J. Barnes; Ryan J. Hansen; Pedro L. Boscan; David C. Twedt; Lauren A. Sullivan (Journal of Veterinary Internal Medicine, 2020)
Abstract Background Dogs infected with canine parvovirus (CPV) have compromised intestinal epithelial barrier integrity. Production of D‐lactate by enteric bacteria may directly reflect disease severity or contribute to metabolic acid‐base status in these dogs. Hypothesis Serum D‐lactate concentration will be increased in CPV dogs compared to healthy controls and correlate with markers of disease severity and acid‐base status. Animals Dogs with CPV undergoing treatment (n = 40) and healthy control dogs (n = 9). Methods Prospective observational study. Dogs with CPV had a baseline and daily CBC, venous blood gas with serum electrolyte concentrations, composite clinical severity score, and serum D‐lactate concentration performed. A single serum D‐lactate measurement was obtained from healthy control dogs. Results The CPV dogs had a higher D‐lactate concentration (mean ± SD) of 469 ± 173 μM compared to controls, 306 ± 45 μM (P < .001). There was no difference in baseline D‐lactate concentrations for CPV survivors (474 ± 28 μM), versus nonsurvivors (424 ± 116 μM; P = .70). D‐lactate concentration decreased over the first 4 days of treatment (−9.6 μM/d; P = .46). Dogs hospitalized for <4 days had lower baseline D‐lactate concentrations compared to those hospitalized ≥4 days (400 ± 178 μM versus 520 ± 152 μM; P = .03). No sustained correlation over time between serum D‐lactate concentration and clinical severity score or recorded acid‐base results. Conclusions and Clinical Importance Serum D‐lactate concentrations are higher in dogs with CPV compared to healthy controls but do not appear to be clinically relevant. No relationship identified between serum D‐lactate concentrations and markers of CPV disease severity, acid‐base status, or outcome.